2001
DOI: 10.1021/ac0011888
|View full text |Cite
|
Sign up to set email alerts
|

A CE−MALDI Interface Based on the Use of Prestructured Sample Supports

Abstract: We have developed an off-line coupling of capillary electrophoresis (CE) to matrix-assisted laser desorption/ionization time-of-flight mass spectrometry(MALDI-TOF-MS) based on CE fraction collection onto prestructured MALDI sample supports. Analyte carryover and detection sensitivity were investigated using a standard peptide mixture. Low femtomole amounts were detected, and no noticeable carryover was discovered. The performance of the method was evaluated with a mixture of tryptic digests of proteins from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 29 publications
0
91
0
Order By: Relevance
“…[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] Only these two configurations are covered in this review, although, brief descriptions of the other three are given in the succeeding paragraphs.…”
Section: Ionization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] Only these two configurations are covered in this review, although, brief descriptions of the other three are given in the succeeding paragraphs.…”
Section: Ionization Methodsmentioning
confidence: 99%
“…68 Johnson et al 69 reported on the identification of more peptides from a mixture of tryptic digests by CE-MALDI, compared to direct MALDI analysis.…”
Section: ·2 Maldi-time-of-flight(tof)-msmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively so-called hydrophobic anchor points can be applied, which utilizes a hydrophilic spot surrounded by a hydrophobic surface. As a large volume is deposited on the anchor point, the sample is enriched on the predefined spot area through the evaporation process [55]. Such target plates are now commercially available from Bruker Daltonics and Micromass.…”
Section: Sample Preparation -Microstructure Utilizationmentioning
confidence: 99%
“…[36][37][38][39][40][41][42][43][44][45][46][47][48] Coupling of MALDI with liquid chromatography, capillary electrophoresis (CE) and gel chromatography is a way to extend its applicability. 32,[49][50][51][52][53][54][55][56][57][58] The possibility to attain the sensitivity of physical limits (a few atoms or molecules) by laser-assisted reflectron TOF-MS has been stated. 59 The precision of the detection and quantification of metal isotope ratios comparable to ICP-MS and thermal ionization mass spectrometry (TIMS) has been reported.…”
Section: An Overview Of Analytical Applications Of Tof-ms Analyzersmentioning
confidence: 99%